Business Communication Strategy of PT Telekomunikasi Selular Surabaya Branch in Sponshorship Negotiation Process - Ira Datus Salamia; Chitra Laksmi Rithmaya (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
34In the face of increasingly competitive business environments, companies must develop effective communication strategies, particularly in establishing sponsorship collaborations. This study aims to examine the business communication strategies implemented by PT Telekomunikasi Selular (Telkomsel) Surabaya Branch in the sponsorship negotiation process with potential partners. The research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The findings reveal that Telkomsel’s communication strategy involves systematic stages, the application of the 7C principles, and adaptive interpersonal approaches tailored to partner characteristics. Key success factors in negotiation include message clarity, value relevance, and the ability to build long-term relationships. Meanwhile, communication barriers such as perception gaps, mismatched expectations, and cultural challenges are among the obstacles encountered. Telkomsel addresses these challenges through clarification, proposal revisions, and two-way communication. These findings reinforce the importance of structured communication planning in building mutually beneficial business partnerships.